Implementasi Pengelolaan Tanah Desa Berbasis Akad Ijarah dalam Upaya Peningkatan Kesejahteraan Masyarakat Desa Bulusari - Ria Rohma Setyawati; Renny Oktafia (Jurnal Ilmiah Ekonomi Islam, 2021)
Abandoned village land is used for community welfare, one of which is used to build people's markets. Where the people's market is useful for utilizing existing facilities, as well as providing opportunities for the surrounding community to increase income as well as creating jobs for people who are unemployed. And from there the Village Officials create a people's market to be rented out to local people who want to trade. The purpose of this study was to determine the application of the ijarah contract and the impact on the welfare of the community. This study uses a qualitative method with a case study approach that aims to obtain information directly from informants based on the current case. The results of this study indicate that the application of village land leases in Bulusari Village is in accordance with Islamic law even though at the time the agreement took place there was no third party to be a witness. As for the impact on Village Officials as land administrators and tenants, this system can improve the welfare of indicators of religion, life, mind, descent and property.